Uji Aktivitas Antioksidan Daging Buah Bisbul dan Batang Buah Naga Merah Menggunakan Metode 1,1-Diphenyl-2-Picrylhydrazin - Wientarsih, Ietje; Prasetyo, Bayu Febram; Kurniawan, Ahmad; Hanifah, Fikri (Jurnal Veteriner; Vol 21 No 4 (2020)DO - 10.19087/jveteriner.2020.21.4.596, 2020)
Bisbul ( Diospyros discolor Willd.) is a plant of the Ebenaceae family and red dragon ( Hylocereus polyrhizus ) is a plant of the Cactaceae family. Bisbul and red dragon have bioactive compounds are flavonoids that act as antioxidants. The purpose of this study was measure antioxidant activity from ethanol extract of bisbul pulp and ethanol extract of red dragon fruit stem by DPPH method ( 1,1-diphenyl-2-picrylhydrazin ). Extraction by maseration method and using 96% ethanol as solution. Antioxidant activity assay using the immersion method of DPPH measured absorption at a wavelenght 517 nm and compared with vitamin C. The result showed that the ethanol extract of bisbul pulp (IC 50 46.00 ìg/mL) more strong antioxidant activity compared the ethanol extract of red dragon fruit stem (IC 50 1020.96 ìg/mL).